2012
DOI: 10.1007/s11695-012-0680-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Selenium in Roux-en-Y Gastric Bypass and Gastric Banding Surgery

Abstract: This study shows that RNY gastric bypass and laparoscopic adjustable gastric banding procedures, and accompanying dietary restrictions, increases the risk for disturbances of selenium and GTP homeostasis. Consideration for selenium supplementation at higher levels than the current RDA of 55 mcg daily during the first 3 months and perhaps longer should be studied further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 9 publications
2
12
0
1
Order By: Relevance
“…Similar findings for selenium levels after bariatric surgery, with early postoperative decrease and subsequent normalization have also been reported in previous studies [16]. However, another study has reported decreased selenium levels long-term after bariatric surgery compared to matched controls who did not receive bariatric operation [27].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar findings for selenium levels after bariatric surgery, with early postoperative decrease and subsequent normalization have also been reported in previous studies [16]. However, another study has reported decreased selenium levels long-term after bariatric surgery compared to matched controls who did not receive bariatric operation [27].…”
Section: Discussionsupporting
confidence: 88%
“…Severe selenium deficiency can cause symptoms and diseases including myopathy, cardiomyopathy, arrhythmia, muscle wasting, impaired immunity, low thyroid function, loss of skin and hair pigmentation, whitened nail beds, and progressive encephalopathy [15,16]. On the other hand, zinc deficiency has been reported to cause diarrhoea, emotional disorders, weight loss, intercurrent infection, bullous-pustular dermatitis, and hypogonadism in males [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…We also found a decrease in selenium serum concentrations and selenium deficiency in 46 % of patients, as well as a drop in zinc serum concentrations and zinc deficiency in 15 % of patients. These values are in line with previously published selenium and zinc deficiency rates after RYGB for obese patients [22][23][24][25]. The decrease can be explained by the bypassing of the selenium resorption site in the duodenum and proximal jejunum [26].…”
Section: Discussionsupporting
confidence: 91%
“…Recommendations for prophylactic vitamin and trace element supplementation include oral or sublingual administration of 1 mg of B 12 daily or intramuscular administration of 1 mg of B 12 monthly, 800 μg to 1 mg of folic acid daily, up to 60 mg of oral zinc daily, 36-65 mg of elemental iron daily, at least 3,500 IU of vitamin A daily, 2,000 IU of vitamin D 3 along with 1,500 mg of calcium daily and vitamin D 2 at a dose of 50,000 IU weekly [11] and at least 55 μg of selenium daily [12]. Occasionally, skin lesions are the first indication of vitamin or trace element deficiency and should trigger further research from a dermatological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…This may become more prominent 3 months after surgery on average, thus selenium supplementation during this time period seems reasonable [27]. Selenium deficiency has been associated with skin dryness, erythematous scaly plaques, cheilitis and light-colored hair [15].…”
Section: Discussionmentioning
confidence: 99%